2020
DOI: 10.1177/0963721420964147
|View full text |Cite
|
Sign up to set email alerts
|

A Developmental-Science Perspective on Social Inequality

Abstract: Many people believe in equality of opportunity but overlook and minimize the structural factors that shape social inequalities in the United States and around the world, such as systematic exclusion (e.g., educational, occupational) based on group membership (e.g., gender, race, socioeconomic status). As a result, social inequalities persist and place marginalized social groups at elevated risk for negative emotional, learning, and health outcomes. Where do the beliefs and behaviors that underlie social inequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(105 citation statements)
references
References 33 publications
4
101
0
Order By: Relevance
“…For example, when told there was an unequal distribution of school supplies between students of different racial backgrounds, older children (i.e., 10-to 11-yearolds) were more likely than their younger counterparts (i.e., 5-to 6-year-old) to judge the distribution as unfair, rectify the inequality by giving more resources to the disadvantaged racial group, and cite equal access and the correction of past inequalities as their reason for doing so . Moreover, adolescents are capable of providing structural explanations of social inequalities and seek to rectify inequality when they know that it is rooted in structural discrimination (Elenbaas et al, 2020). These findings suggest that adolescents develop a more complex understanding of inequality and ability to recognize structural inequity which may influence their attribution of racism to systems and structures.…”
Section: Moral Developmentmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, when told there was an unequal distribution of school supplies between students of different racial backgrounds, older children (i.e., 10-to 11-yearolds) were more likely than their younger counterparts (i.e., 5-to 6-year-old) to judge the distribution as unfair, rectify the inequality by giving more resources to the disadvantaged racial group, and cite equal access and the correction of past inequalities as their reason for doing so . Moreover, adolescents are capable of providing structural explanations of social inequalities and seek to rectify inequality when they know that it is rooted in structural discrimination (Elenbaas et al, 2020). These findings suggest that adolescents develop a more complex understanding of inequality and ability to recognize structural inequity which may influence their attribution of racism to systems and structures.…”
Section: Moral Developmentmentioning
confidence: 93%
“…Early adolescence (i.e., ages 9 -14) is a key developmental period for the development of antiracism among White youth. The development of more advanced socio-cognitive abilities (e.g., empathy, social perspective-taking) allow adolescents to think more abstractly about race, more critically examine social issues, and develop a more complex understanding of inequality (Elenbaas et al, 2020;Quintana, 2008). Promoting anti-racism early in life is likely to facilitate more and longer-term benefits at both the individual-(e.g., positive interactions with people of color) and structural-(e.g., political engagement) level.…”
Section: Anti-racism In Childhood and Adolescencementioning
confidence: 99%
“…Indeed, the discriminatory ethnic experience could be mainly based on the socioeconomic exclusion of these marginalized groups, and in general, it has been suggested that the persistence of social inequality place marginalized groups at high risk for different negative outcomes (i.e., emotional, health, learning, etc. ; Elenbaas, Rizzo, & Killen, 2020). We argue that the lack of a cross‐ethnic friendship network might be one of these negative consequences.…”
Section: Prejudice Towards Low‐status Incomers: the Interplay Between Social Class And Ethnicitymentioning
confidence: 99%
“…The present study contributes to this emerging research area in a few ways: First, the research on structural attributions often involves explicitly telling children about the cause of a given disparity (e.g., Hussak and Cimpian, 2015;Sutherland and Cimpian, 2019;Rizzo et al, 2020;Dunlea and Heiphetz, 2021). However, as recent reviews have pointed out (Elenbaas et al, 2020), children rarely receive explicit explanations for disparities; instead, they are often faced with causally-ambiguous disparities and left to their own devices to make sense of them. In the current study, children were not provided with explicit explanations for the presented disparities.…”
Section: Personal Attributions and Prejudice Developmentmentioning
confidence: 99%
“…Prior work on children's structural attributions has primarily involved teaching children explicitly that disparities that were caused by either intrinsic or extrinsic factors (e.g., Hussak and Cimpian, 2015;Sutherland and Cimpian, 2019;Rizzo et al, 2020;Dunlea and Heiphetz, 2021). However, recent reviews have pointed out that children rarely receive explicit information about causes of disparities (Elenbaas et al, 2020). Instead, children may encounter disparities with ambiguous causal origins and are left to their own devices to form attributions for them.…”
Section: Impact Of Framing On Attributionsmentioning
confidence: 99%